التنوع الحيوي في النظام البيئي المدني- حالة دراسة: مدينة اللاذقية (Latakia University Journal -Biological Sciences Series, 2019)
يعد الفقد السريع للتنوع الحيوي ظاهرة عامة نتيجة تعديل المسكن والنمو السكاني السريع الذي سبب تطور المدن وتوسعها مقابل تراجع الأنظمة البيئية الطبيعية, وأحد الخيارات هو تعزيز التنوع الحيوي في النظام البيئي المدني. تهدف هذه الدراسة إلى تقدير التنوع الحيوي (تنوع النباتات والطيور) في مدينة اللاذقية. أظهرت الدراسة وجود 53 نوعاً نباتياً تنتمي إلى 29 فصيلة وكان التين اللامع Ficus nitida والدفلة Nerium oleander من أكثر الأنواع استعمالاً, كما بينت الدراسة وجود 18 نوعاً طيرياً, أربعة أنواع مقيمة بشكل دائم في هذه الحدائق. لم تظهر الدراسة وجود علاقة ارتباط بين مساحة الحدائق والغنى النوعي, في حين وجد ارتباط بين طول الشارع والغنى النوعي. بينت الدراسة أن بعض الفصائل والأجناس والأنواع مستخدمة بنسب أكثر من المسموح بها. Rapid loss of biodiversity is a global phenomenon; many factors e contribute to this loss including habitat modification, growth of human population which caused urban development and expanding cities, and on the other hand decrease of natural ecosystems, so an available alternative is promoting biodiversity in the urban ecosystems. This research aims at evaluating plants and birds diversity in Latakia city. The study recorded 53 plant species belonging to 29 family, Nerium oleander and Ficus nitida were the most two frequent species, also 18 bird species, 4 species are resident in the parks. The study did not show relationship between parks area and plant species richness, but it found a relationship between length of the street and species richness. The study indicated that some families and genus, have been used in proportion higher than the allowed value.